Local Autonomy: State-Centered Government Wrapped in Citizen-Centered Governance in the Tourism Development - Wijayanto, Purbayakti Kusuma; Zauhar, Soesilo; Hakim, Luqman; Said, Abdullah (JPAS (Journal of Public Administration Studies), 2020)
This city is called Batu Tourism City. Nine great modern-made tourism objects exist in this city. Four million tourist visits occur in this city. All built only since 16 years of local autonomy that they get. But many people said, "That is not ours." "We can't do anything.â€ â€œMiserable." Some authoritative actions of the local government appear to be different from the established policies. There was a conflict from communitiy elements. How exactly is the management of tourism development carried out? The results found four patterns in the management of tourism development. Tourism policy preferences regulated through participatory planning, tourism development is set to improve people's welfare, tourism development is facilitated by the Mayor and the City Government of Batu, and tourism development tends to be carried out by private capitalists through the entrance of tourism business investment. State-Centered Government Wrapped in Citizen-Centered Governance. Local autonomy that occurs is a type of autonomy in which the local government relies on its strong power to translate preferences into public policy under conditions of divergence. A type of autonomy in which public officials use the autonomy authority and the opportunities to free themselves from obstacles from social actors who have different preferences.